CD34+ cell count predicts long lasting life in the oldest old. (June 2017) - Mandraffino, Giuseppe; Aragona, Caterina Oriana; Basile, Giorgio; Cairo, Valentina; Mamone, Federica; Morace, Carmela; D'Ascola, Angela; Alibrandi, Angela; Lo Gullo, Alberto; Loddo, Saverio; Saitta, Antonino; Imbalzano, Egidio
Highlights: Additional insights about the predictive role of CD34 + CPCs in oldest old. In old subjects classic CV risk factors and HDL-C levels lose their predictive ability. Life expectancy, in terms of age-reached, seems to be associated mainly with CD34 + CPCs. Inflammatory markers and CV risk factors seem to not significantly affect life expectancy in oldest subjects. The contribution of CVRFs and chronic inflammation in affecting longevity might be overcome by higher CD34 + CPC number. Abstract: Circulating progenitor cells (CPCs) represent a pool of cells capable of differentiating into mature cells of different organs and systems, promoting tissue maintenance and repair. Among CPCs, CD34 + cells (CD34 + CPCs) seem to predict outcome in CV disease, also in elderly people. A decline in CD34 + CPCs was reported with advancing age. Moreover, aging is associated with a state of chronic inflammation, influencing life expectancy. Our purpose was to investigate a 10-year predictive ability of CD34 + CPCs, inflammatory marker levels, classic CV risk factors (CVRFs), and Framingham Risk Score (FRS) in a population of healthy, self-sufficient octogenarians. We found that baseline CD34 + CPCs was strongly associated with mortality, showing a significant difference in CD34 + CPC numbers between deceased and living patients. Moreover, by dividing our patients into tertiles based on age reached, this difference was more remarkable the higher the age reached. Regressive analyses suggested that the chances of reaching an older age depend on higher CD34 + CPCs at baseline and are not significantly affected by inflammatory markers levels, FRS, CVFRs, or HDL-C levels. We found that higher CD34 + CPCs predict longer life also in the oldest old, providing additional insights on the predictive role of CD34 + CPCs in subjects aged 80 years or more.